Acute stunning effect of hemodialysis on myocardial performance: A three‐dimensional speckle tracking echocardiographic study. Issue 10 (5th May 2020) - Guler, Hasan Selim; Tulunay Kaya, Cansin; Kumru, Gizem; Kosku, Hakan; Ozyuncu, Nil; Sengul, Sule; Kutlay, Sim
Abstract: The effects of acute changes during hemodialysis (HD) on the myocardium are not yet known. The invention of three‐dimensional speckle tracking echocardiography (3DSTE) has offered clinicians a new method to assess the movements of ventricular segments simultaneously in three spatial directions. The aim of this study was to evaluate the effect of first weekly standard HD process on the left ventricle (LV) and right ventricle (RV) global and regional myocardial function in patients with normal left ventricle ejection fraction using 3DSTE‐derived indices. Patients (n=38) receiving maintenance HD in our clinic who have no known cardiovascular disease are examined just before and after a HD session using 3DSTE. Demographic and comorbidity data, renal replacement treatment characteristics, and laboratory test results are recorded. 3DSTE analysis is performed to calculate the LV global longitudinal, circumferential area and radial peak systolic strain, as well as RV septum and free‐wall longitudinal strain and fractional area change. Patients are aged 52.8 ± 13.6 years and 52.6% of them are male. Mean dialysis duration is 56 months. The LV strain values of the patients changed markedly before and after HD (GLS: −14.2 ± 5.2, −11.1 ± 4.6 [ P < .001], GCS: −14.8 ± 4.2, −12.4 ± 5.28 [ P < .009]; GRS: 41.5 ± 16, 33.3 ± 16.5 [ P = .003]; AREA −24.7 ± 7.2, −20.1 ± 7.6 [ P = .001], respectively). We could not demonstrate any improvement in RV strain values before or after HD. LV strain values are positively correlated with blood pressure variability during the dialysis sessions. LV function is preserved better after HD in patients on beta or calcium channel blocker therapy compared to those who do not use these agents ( P < .001, P < .01, respectively). HD treatment results in deterioration in all LV strain directions but not in RV. Strain assessment may improve vascular risk stratification of patients on chronic HD.